A "Hole Punched Plate" method for easy generation and harvesting of microconidia in the dermatophyte Trichophyton rubrum. Issue 7 (July 2018) - Siede, Wolfram
Abstract: Handling of the medically important dermatophyte Trichophyton rubrum in the laboratory typically requires the generation of spores — for storage, treatment and plating when needed. The described method allows technically simple but efficient generation and harvesting of microconidia by cutting holes in Sabouraud dextrose agar medium that is covered by a mature T. rubrum mycelium.